Redelimitation of Astraea lobata (Euphorbiaceae) and other taxonomic rearrangements in Astraea - Silva, Otávio Luis Marques Da; Dias, Pedro; Riina, Ricarda; Cordeiro, Inês (Phytotaxa, 2019)
Astraea lobata is the most complex species within Astraea due to its wide distribution range and lack of clear diagnostic characters in its current delimitation. Based on an extensive revision of herbarium specimens and field observations, we recognize three more entities, including two new combinations, apart from A. lobata s.s.: A. surinamensis and A. trilobata, two weedy species distributed both in the New and Old World, and A. paulina, which is only known from Brazil and Bolivia. We also reestablish A. klotzschii as distinct from A. macroura and synonymize A. aureomarginata and A. hauthalii under A. cincta.